Durable antibody and effector memory T cell responses in breastmilk from women with SARS-CoV-2 - Narayanaswamy, Vignesh; Pentecost, Brian T.; Telfer, Janice C.; Burnside, Amy S.; Schneider, Sallie S.; Alfandari, Dominique; Baker, Ryan L.; Saiju, Aman; Nodiff, Sam; Arcaro, Kathleen F. (Frontiers in Immunology, 2022)
Background Given that only 25% of pregnant women elect to receive a COVID-19 vaccine, maternal SARS-CoV-2 infection remains an important route of conferring protective passive immunity to breastfed infants of mothers who are not vaccinated. Methods We enrolled 30 lactating participants between December 2020 and March 2021 who had a positive PCR-test and their first COVID-19 symptoms within the previous 21 days. Participants were asked to provide serial bilateral milk samples at 12 timepoints ( every 3 days) over a period of 35 days. A second set of samples was collected at least four months after the beginning of the first set. Participants also were asked to provide their dried blood spots and infant stool samples. All samples were tested for receptor-binding domain (RBD)-specific immunoglobulin (Ig)A, IgG, and IgM. Milk samples were assessed for neutralizing ability against the spike protein and four SARS-CoV-2 variants: D614G, Alpha (B.1.1.7), Beta (B.1.351), and Gamma (P.1). Permeability of the breast epithelium was assessed by measuring the sodium to potassium ions (Na:K) in milk. Using flow cytometry, memory CD4 and CD8 T cells (CD45RO+ and CCR7+/-) and mucosal-homing CD4 and CD8 T cells (CD103+) were determined in cells from milk expressed at 35 days and at least 4 months after their first milk donation. Results Milk antibodies from SARS-CoV-2 positive participants neutralized the spike complex. Milk from 73, 90, and 53% of participants had binding reactivities to RBD-specific IgA, IgG, and IgM, respectively. In contrast to blood spots, which showed increased levels of IgG, but not IgA or IgM, the COVID-19 response in milk was associated with a robust IgA response. Twenty-seven percent of participants had increased breast-epithelium permeability, as indicated by Na:K ≥ 0.6. The percentage of CD45RO+CCR7- effector-memory T cells in the day ≥120 milk samples was significantly higher than day 35 samples (P< 0.05). Conclusions Antibodies in milk from participants with recent SARS-CoV-2 infection and those who recovered can neutralize the spike complex. For the first time we show that breastmilk T cells are enriched for mucosal memory T cells, further emphasizing the passive protection against SARS-CoV-2 conferred to infants via breastmilk.